Experience of phytocomposition application for correction of sleep disturbance in elderly people - F. M. Melikov; I. A. Batura; V. V. Tonkovtseva; A. M. Yarosh; E. S. Koval (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The influence of phytocomposition on the quality of sleep of 23 elderly women, as well as on the psychoemotional state and hemodynamic parameters, was studied. There was a decrease in the time of falling asleep, an increase in the duration of sleep, a decrease in the frequency of nocturnal awakenings, and an increase in the evaluation of the quality assessment of awakening on the 21st day of the phytocomposition application. In addition, there was a significant decrease in anxiety, systolic blood pressure and pulse pressure.